DETERMINAN PENDAPATAN PEREMPUAN PEKERJA INFORMAL (STUDI KASUS PASAR DESA ADAT DI DESA DALUNG) - A. A. Istri Agung Triana Santi; Ni Made Tisnawati (E-Jurnal Ekonomi Pembangunan, 2023)
This observe ambitions to decide the impact partly and concurrently on paintings experience, age, operating capital and wide variety of own circle of relatives dependents at the profits of ladies casual employees (Case Study of Traditional Village Markets in Dalung Village). The statistics used on this observe is number one statistics, specifically via way of means of dispensing questionnaires to casual area ladies employees on the Traditional Village Market in Dalung Village. The populace used on this observe had been all casual area ladies employees withinside the Traditional Village Market of Dalung Village. The overall populace used is eighty lady employees the usage of the approach of figuring out the sample, specifically, Random Sampling. The evaluation approach used on this observe is a couple of linear regression evaluation. The consequences of statistics processing of the a couple of linear regression version located that the consequences of labor experience, age, operating capital and wide variety of own circle of relatives dependents had a vast simultaneous impact at the profits of lady casual employees on the Traditional Village Market in Dalung Village. Partially, paintings experience, operating capital and wide variety of own circle of relatives dependents have a advantageous and vast impact at the profits of lady casual employees on the Traditional Village Market in Dalung Village. The age variable partly has a terrible and vast impact at the profits of casual ladies employees on the Traditional Village Market in Dalung Village.